ANALISIS STRATEGI BERSAING DALAM BISNIS FIXED WIRELESS Studi pada DivisiTelkom Fleksi, PT. Telekomunikasi Indonesia, Tbk - , Moch. Wasiul Hamil, ST; , Prof. Dr. Djoko Susanto, MSA. Ak. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Competition is a must. TELKOM as a state-owned enterprise at the beginning was the sole organizer of the agency responsible for coordinating the domestic telecommunications services. But as global demand since the government enforce the law No.36/1999, the national policy in the telecommunications sector has changed, from the monopoly system to liberalization efforts. Various alternative strategies have been prepared and executed by TELKOM to face competition and cope with declining revenue trends. One strategy that is implemented in early 2003 in the business of wireless phones fixed wireless access (FWA) and launched the product with the brand "Flexi" who managed the Division of Telkom Flexi (DTF). Businesses are expected to be the engine of new revenue in the face of this competition was able to maintain positive earnings trend over the past six years only to then again decrease. Intense competition and changing business constellations inevitably be the cause of the business will not live long without the effort of developing a business strategy that is always adaptable and competitive in the industry. Writing the final work of this thesis aims to analyze and review of competitive strategy in business DTF in order to compete effectively in the FWA industry with a few things: 1. Analyzing the business environment in terms of external and internal, as well as the competitive forces in the industry. 2. Do matching of the alternative strategy, as well as an analysis of alternative business strategies to compete in accordance with environmental conditions. 3. Provide recommendations for effective strategies to manage the business in order to compete in the FWA wireless industry's mobile phone. This type of descriptive research is qualitative, drawing on case studies on the DTF object. -Competitive strategy analysis tools that are used include: EFE and IFE, Porter's Five Forces Model, IE Matrix, Grand Strategy Matrix, SWOT, and QSPM (Quantitative Strategic Planning Matrix). The results of the analysis and assessment in this study showed that the FWA business due to regulatory, technological, and business competition with cellular operator products have very heavy pressure, and in less favorable conditions. Mastery of a relatively large market share and high customer growth is less able to make DTF continued to grow, but to do sharpening as well as changes in business strategy, as will be described in this thesis.